Quality by Design-Based Methodology for Development of Titanate Nanotubes Specified for Pharmaceutical Applications Based on Risk Assessment and Artificial Neural Network Modeling - Ranim Saker; Géza Regdon; Krisztina Ludasi; Tamás Sovány (Pharmaceutics)
Background: Nanotechnology has been the main area of focus for research in different disciplines, such as medicine, engineering, and applied sciences. Therefore, enormous efforts have been made to insert the use of nanoparticles into the daily routines of different platforms due to their impressive performance and the huge potential they could offer. Among numerous types of nanomaterials, titanate nanotubes have been widely recognised as some of the most promising nanocarriers due to their outstanding profile and brilliant design. Their implementation in pharmaceutical applications is of huge interest nowadays as it could be of fundamental importance in the development of the pharmaceutical industry and therapeutic systems. Methods: In the present work, a risk assessment-based procedure was developed and completed using ANN-based modeling to enable the design and fabrication of titanate nanotube-based drug delivery systems with desired properties, based on the critical analysis and evaluation of data collected from published articles regarding titanate nanotube preparation using the hydrothermal treatment method. Results: This analysis is presented as an integrated pathway for titanate nanotube preparation and utilization in a proper way that meets the strict requirements of pharmaceutical systems (quality, safety, and efficacy). Furthermore, a reasonable estimation of the factors affecting titanate nanotube preparation and transformation from traditional uses to novel pharmaceutical ones was established with the aid of a quality by design approach and risk assessment tools, mainly an Ishikawa diagram, a risk estimation matrix, and Pareto analysis. Conclusions: To the best of our knowledge, this is the first article using the QbD approach to suggest a systematic method for the purpose of upgrading TNT use to the pharmaceutical domain.